Treatment outcome of dome osteotomy of the pelvis combined with trochanteric advancement for sequelae of Perthes' disease - Asep Santoso; Pramod Shaligram Ingale; Ik-Sun Choi; Young-Rok Shin; Kyung-Soon Park; Taek-Rim Yoon (Acta Orthopaedica et Traumatologica Turcica)
Objective: Disparity in size between femoral head and acetabulum could promote premature degeneration of the hip joint. The purpose of this study was to report the results of Kawamura's dome osteotomy for acetabular dysplasia due to sequelae of Perthes' disease. Patients and Methods: Fourteen patients (14 hips) operated between 1999 and 2012 were retrospectively reviewed. There were 9 males and 5 females with a mean age of 29 years (range, 15–54 years). Functional and radiological results were reviewed at mean follow-up of 9 years (range, 4–12 years). Results: Pain relief was obtained in 13 of 14 (92.8%) patients postoperatively. Good to excellent functional outcome was obtained in 10 of 14 (71.4%) patients. Mean Harris hip score was improved from 63 to 84 (p < 0.05) at the final follow-up. Improvement of limping gait was observed in 10 of 14 (71.4%) patients. Center edge angle improved from mean 24° (11–36°) preoperatively to mean 35° (27–46°) postoperatively (p < 0.05), acetabular angle improved from mean 43° (36–49°) preoperatively to mean 37° (32–44°) postoperatively (p < 0.05), acetabular head index improved from mean 69% (50–83%) preoperatively to mean 85% (73–100%) postoperatively (p < 0.05). Progression of arthrosis stage occurred in 3 of 14 (21%) patients. None of the hip with preoperative Stulberg III, 2 of 9 hips with Stulberg IV and 2 of 2 hips with Stulberg V needed conversion to total hip arthroplasty during the follow-up. Conclusion: Dome osteotomy of the pelvis combined with trochanteric advancement could give a reasonable treatment outcome for acetabular dysplasia due to Perthes' disease at mid to long-term follow-up. Advanced stage of arthrosis, preoperative Stulberg V and no improvement of limping gait after the surgery possibly associated with poor outcome. Level of evidence: Level IV, therapeutic study. Keywords: Dome osteotomy, Trochanteric advancement, Acetabular dysplasia, Perthes' disease, Sequelae